Sistem Pengambilan Keputusan Pemberian Kredit Pemilikan Rumah Menerapkan WASPAS - Sitti Nur Alam (JURIKOM (Jurnal Riset Komputer), 2022)
Decision Support System (DSS) is an interactive information system that provides information, models and manipulates information, or helps someone make accurate and targeted decisions. So a decision support system is needed to determine the eligibility of customers to take home equity loans (HPR). In this study, the Comprehensive Assessment Method or WASPAS is used to determine the eligibility of prospective mortgage holders. Several criteria are used to make decisions, including age, income, debt, occupation, and credit rating.